MODEL PENGEMBANGAN PERMAINAN BOLA BASKET EMPAT SASARAN TEMBAK BERGERAK DALAM PENJASORKES (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The research problem is whether the Penjasorkes learning model through modificationfourbasketball games shooting moving targets can improve learning. The purpose of this studywas to determine the results of the Penjasorkes learning models through four basketball gamesshooting moving targets are modified in fifth grade elementary school students can improvePenjasorkeslearning. This study uses a research-based development. Based on the results ofa small trial group showed a response to product modification basketball game four movingtarget shooting is good (77%). Results of field trials showed response to product modificationbasketball game four shooting moving targets covering aspects of psychomotor, cognitive andaffective been good (88%). Studies and suggestions of this research is the development of productmodification basketball game four viable moving target shooting used to study materialsas it gets good reception by students and can increase the activity of students during learning.Therefore, it can be submitted suggestions: Teachers should consider the use of the productPenjasorkes modification basketball game four moves as an alternative target shooting in deliveringlearning basketball in fifth grade elementary school.